EVALUASI PROGRAM KAMPUNG KELUARGA BERENCANA DI KOTA DENPASAR - Tri Mardani, Ni Komang; Winaya, I Ketut; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2020)
ABSTRACT The Village Family Planning Program aims to overcome thexproblems of population,xfamily planning (KB),xfamily development andximprove the quality of life of the community.this study purpose to determine how the evaluation of family planning program in the Denpasar City. This study uses xevaluation criteria according toaWilliam Dunn, namely, efficiency,xeffectiveness,xadequacy, alignment, xresponsiveness, and xaccuracy. The results based criteria show that the Family Planning Village on the effectiveness criteria has xbeen able to achieve the goals set.The leveling criteria have not yet reached levels in terms of location and service.xThe responsiveness criteria in the satisfaction level indicator show a xpositive xresponse and thexcommunity feelsxsatisfied and the community feels thexpositiveximpact of the existence of this Family Planning Village. On the criteria ofxthe accuracy of the villagexfamily planning program, it has become an appropriate means of improving community welfare. Keyword : Evaluation, Program, The Family Planning Village.